Analisis Aspek Keadilan PPH UMKM: Studi Komparasi di Indonesia, Malaysia, dan Australia - Muhammad Rheza Ramadhan; M. Syahrizal Aditya Wibowo (Sekolah Tinggi Ilmu Bisnis Kumala Nusa Yogyakarta, 2022)
Abstract: Micro, Small and Medium Enterprises (MSMEs) play an important role in the Indonesian economy, because it contributes greatly to Indonesia's GDP and creates a large revenue potential if viewed from a taxation perspective. The government has taken an important step to tax it, namely final tax rate in Government Regulation Number 23/2018. However, the imposition of this final income tax is considered burdensome for some MSME taxpayers, especially for stagnant and undeveloped MSMEs. The purpose of this study is to analyze MSME taxes fairness and comparation of its taxation in Malaysia and Australia. The method used by the author in this case is literature study and interviews. Data analysis shows that MSMEs taxation fairness in each country depends on government policy and its conditions. To make its taxation policy more fair, needs to be a good relationship between taxpayer and tax authorities in the form of giving incentives or guidances so taxpayer will pay taxes more obedient and feel fair. Keywords: MSME; Final tax; Fairness